External nutrients fattening promotes hepatopancreases development, metabolism, nutrient deposition and flavor yield during the maturation stage in female Chinese mitten crab (Eriocheir sinensis) - Changyou Song; Jianxiang Chen; Jiyan He; Miaomiao Xue; Pao Xu; Huiming Ding; Ningyuan Wu; Ruicheng Zhao; Gangchun Xu; Hongxia Li (Aquaculture Reports)
The nutritive value and maturity status of hepatopancreases dominates the quality of Chinese mitten crab, Eriocheir sinensis. However, the underlying function and regulatory mechanism, as well as the external nutrient factors on the development of hepatopancreases in different growth stages of E. sinensis remains unclear. In this study, we first revealed the function of hepatopancreases feeding with iced trash fish (ITF) during the whole culture period; and further investigated the underlying mechanism on nutrient deposition and flavor yield feeding with formulated feed (FEED) in replacement of ITF in female E. sinensis. From the results, growth performance and metabolism indicate E. sinensis was robustly developed, and ITF promotes growth and hepatopancreases development during the maturation period. Meanwhile, activation of fatty acid and amino acid metabolism in hepatopancreases resulted in depletion of monounsaturated fatty acids (MUFAs) but promoted protein deposition during the maturation stage. Integrated analysis of transcriptome and metabolome reveal metabolism, biosynthesis, and flavor presentation were intensively active during maturation, evidenced by the expression of key genes of ALDH, TBXAs, HADHA, UPB1, CYP2, GST, and γ-GT-X1; as well as the key metabolites of GMP and IMP. Additionally, substitution of ITF with FEED further confirm full price artificial feed could meet the nutrient requirements during the maturation period, evidenced by the growth performance, fatty acid and amino acid derived nutrient and flavor yield in hepatopancreases. In conclusion, nutrient and flavor deposition was associated with the fast development of hepatopancreases, and fatten with full price compound feed contributes to the nutrient requirement and flavor yield during the maturation stage.